Neuroprotective effect of granulocyte colony-stimulating factor after focal cerebral ischemia - Schäbitz, Wolf-Rüdiger; Kollmar, Rainer; Schwaninger, Markus; Jüttler, Eric; Bardutzky, Jürgen; Schölzke, Marion Nicola; Sommer, Clemens; Schwab, Stefan (Stroke, 2003)
Background and Purpose: The potential neuroprotective effect of the granulocyte colony-stimulating factor (G-CSF) after glutamate-induced excitotoxicity in cell culture and after focal cerebral ischemia in rats was studied. We hypothesized the existence of the G-CSF receptor (G-CSFR) as a main G-CSF effector on neurons, and immunohistochemistry, immunoblotting, and polymerase chain reaction were performed. The G-CSFR-mediated action was studied by activation of signal transducer(s) and activator(s) of transcription-3 (STAT3) in the periphery of the infarction. Methods: Neuroprotection of various G-CSF concentrations on glutamate-induced excitotoxicity was studied in cell culture. In vivo, ischemia was induced by use of a suture occlusion model of the middle cerebral artery (90-minute occlusion) in the rat. Thirty minutes after the induction of ischemia, the animals (n=12 per group) received G-CSF at 60 μg/kg body wt IV for 90 minutes or vehicle (saline). Infarct volume was calculated on the basis of 2,3,5-triphenyltetrazolium chloride staining 24 hours after ischemia. Expression of the G-CSFR was studied by immunohistochemistry and verified by reverse transcription-polymerase chain reaction and immunoblotting. Expression of STAT3 was determined by immunohistochemistry. Results: In cell culture, G-CSF exhibited a significant neuroprotective effect after glutamate-induced excitotoxicity (P<0.05). A G-CSF concentration of 10 ng/mL was maximally effective, resulting in a nearly complete protection. In vivo, G-CSF reduced infarct volume to 47% (132.0±112.7 mm3 versus 278.9±91.6 mm3 [P<0.05] in the control group). Immunohistochemistry, Western blotting, and reverse transcription-polymerase chain reaction revealed the existence of G-CSFRs in neurons and glial cells. Animals treated with G-CSF significantly upregulated STAT3 in the periphery of the infarction compared with control animals (P<0.05). Conclusions: G-CSF achieved a significant neuroprotective effect in cell culture and after intravenous administration after stroke. Increased STAT3 expression in the penumbra of G-CSF-treated rats suggests mediation by G-CSFR.
Gesehen am 29.03.2021